Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/2162402x.2017.1312044
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation of anti-CD73 mechanisms in control of primary tumors and metastases

Abstract: The emerging role for CD73 in driving cancer growth and metastasis has presented opportunities to develop anti-CD73 monoclonal antibodies (mAbs) in the treatment of human cancers. Blockade of CD73 by antagonistic CD73 mAbs ameliorates tumor growth and metastasis via the inhibition of enzymatic and non-enzymatic CD73 pathways. In this study, we investigated whether Fc-receptor cross-linking represented a non-redundant mechanism by which anti-CD73 mAbs exert potent suppression of solid tumors and metastases. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
(42 reference statements)
0
13
1
Order By: Relevance
“…However, despite all that we have discussed so far, not all effects observed following Abcc6 silencing were mimicked by treatment with probenecid. Unlike what was previously observed in Abcc6 knockdown HepG2 cells [14], probenecid did not block cell cycle and cellular senescence, probably because it has a lesser impact on cellular metabolism, compared to what happens in response to gene silencing.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…However, despite all that we have discussed so far, not all effects observed following Abcc6 silencing were mimicked by treatment with probenecid. Unlike what was previously observed in Abcc6 knockdown HepG2 cells [14], probenecid did not block cell cycle and cellular senescence, probably because it has a lesser impact on cellular metabolism, compared to what happens in response to gene silencing.…”
Section: Discussioncontrasting
confidence: 92%
“…The ecto-5 -nucleotidase CD73 is able to catalyze the conversion of extracellular AMP to adenosine and phosphate; it is the main source of extracellular adenosine in all tissues in which ATP is poorly present in extracellular fluids [10,11]. CD73 is considered a key regulator in some cancer processes such as drug resistance, tumor metastasis, and tumor angiogenesis [12,13], therefore is an excellent candidate for cancer therapy [14][15][16]. In previous studies, we have reported that knockdown of Abcc6 in hepatocarcinoma cancer cells (HepG2), or the inhibition of its activity lead to the downregulation of NT5E gene, which codifies for the CD73 protein [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies reported that NK cells acquire the expression of CD73 after physical contact with human umbilical cord-derived MSCs or dental pulp stem cells (37,38). In cancer, NK cells from gastrointestinal stromal tumors (GISTs) have been found to express higher levels of surface CD73 (39). Yet, the current understanding of tumor-infiltrating NK cells is unclear with regard to their robustness in phenotype and function.…”
Section: Nk Cell Signature Influences the Predictive Value Of Cd73 Gementioning
confidence: 99%
“…Three CD73 blocking antibodies have been entered into clinical trials (i.e., BMS-986179, CPI-006, and MEDI9447). Compared with small-molecule inhibitors, anti-CD73 mAbs offer the possibility of directly targeting both enzymatic and non-enzymatic CD73 pathways (148). In vitro data showed that MEDI9447 (human IgG1 variant) could inhibit the enzymatic activity of both soluble- and membrane-bound CD73 through prevention of the conformational transition of CD73 to an active state, and could induce internalization of membrane-bound CD73, and restore T-cell proliferation from the inhibition by AMP (149, 150).…”
Section: Immune Checkpoint Molecules and Their Therapeutic Antibodiesmentioning
confidence: 99%